Survival or Prophecy? - O'Dell, Colman 1928-2017 (2003)
Reviews the non-fiction book 'Survival or Prophecy? The Letters of Thomas Merton and Jean Leclercq,' edited by Patrick Hart.
Keywords: Nonfiction; Prophecy; Survival or Prophecy? (Book); Rezension